Time-temperature profiles effect on thermoluminescence glow curve formation of germanium doped optical fibres - Muhammad Safwan Ahmad Fadzil,; Noramaliza Mohd Noor,; Nizam Tamchek,; Ung, Ngie Min (Penerbit Universiti Kebangsaan Malaysia, 2022)
The development of optical fibres technology grows in response to seeking a radiation detector with better thermoluminescence (TL) performance. Concerning the dosimetric characterization study by previous researchers, this research work has widened the exploration to optimize the time-temperature profile (TTP) in connection with the glow curve formation of the optical fibres. Two forms of germanium (Ge) doped optical fibres, namely cylindrical optical fibre (CF) and flat optical fibre (FF) were fabricated, and the TTP were investigated prior to commissioning the optical fibres for fieldwork. CF and FF were irradiated to the dose of 2 Gy using a 6 MV linear accelerator. Various TTP profiles, including preheat temperature, preheat time, acquisition temperature rate, and acquisition time were varied to determine the best thermal profile for the CF and FF based on the glow curve formations. Out of 4 parameters, an increase in preheat temperatures ranging from 40 to 120 °C caused a significant variation in the glow curve formation, thus possibly giving rise to different TL signals of the optical fibres. The maximum glow peak temperature of CF and FF was unvarying when different preheat temperatures employed. These findings support the conceptual idea that manipulating the optical fibres’ readout system can alter the glow curve formation. Thus, an optimized TTP will provide the correct glow curve configuration for kinetic parameter analysis.